Technology-facilitated sexual violence among Italian youths: validation of the technology-facilitated sexual violence victimization scale - Laura Orsolini; İmran Gökçen Yılmaz-Karaman; İmran Gökçen Yılmaz-Karaman; Kerim Selvi; Salvatore Reina; Giulio Longo; Umberto Volpe (Frontiers in Psychiatry, 2024)
IntroductionTechnology-facilitated sexual violence (TFSV), i.e. the use of digital communication technologies for facilitating sexual violence and harassment, represents a concern due to its exponential growth, particularly among youths. Few studies investigated TFSV, mainly due to the lack of a validated assessment tool, such as the TFSV-Victimization scale (TFSV-VS). Our study aimed to investigate the TFSV phenomenon in a sample of Italian young adults (aged 18-24), through the validation of the Italian translated version of TFSV-VS.MethodsThe study consisted of two phases: 1) validation of the Italian version of TFSV-VS; b) evaluation of TFSV lifetime and during the last 12 months among Italian youths.ResultsIn our sample, 78.6% and 56.1% of subjects reported a lifetime and 12-months TFSV victimization, respectively. Digital sexual (70.4% and 46.6%), gender and/or sexuality-based harassment (43% and 29.6%) are those most represented. A gendered and sexuality-based pattern in lifetime TFSV was observed, mainly observed among females (p=0.005) and sexual/gender minority (SGM)(p=0.001). Being female (p<0.001) and perceiving low social support (p = 0.030) were associated with higher subjective distress related to traumatic TFSV experiences. Being female (p<0.001), younger (p=0.006) and perceiving low social support (p=0.030) were associated with the highest psychological distress due to TFSV.ConclusionsItalian TFSV-VS shows good psychometric properties. Our findings observed a gendered trend of TFSV, by suggesting TFSV as a phenomenon influenced by SGM belonging.